2019
DOI: 10.1186/s41938-018-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Field efficacy of different combinations of Trichoderma harzianum, Pseudomonas fluorescens, and arbuscular mycorrhiza fungus against the major diseases of tomato in Uttarakhand (India)

Abstract: Tomato is one of the major cash crops in the Golapar area of district Nainital in Uttarakhand (India), where farmers are facing the problem of diseases in tomato cultivation. In the present investigation, a survey of tomato fields in the Golapar area of Haldwani block was conducted. The survey revealed the occurrence of late blight, early blight, stem rot, and wilt diseases causing an average loss of 80% to tomato. To counter the above diseases, Trichoderma harzianum (Th43), Pseudomonas fluorescens (Pf173), Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…In contrast, in the study of Colla et al (2015), R. irregularis co-inoculated with T. atroviride enhanced crop growth more than each of the microorganisms alone. Also Kabdwal et al (2019) observed best plant performance when multiple plant-beneficial microorganisms, including T. harzianum and AM fungi, were applied. Since soil-born beneficial microbes play a pivotal role in the functioning of plants by influencing their physiology and development (Mendes et al, 2013), further studies are needed to investigate the possible outcome when a plant is involved in interactions between different beneficial agents, including ectomycorrhizal fungi.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, in the study of Colla et al (2015), R. irregularis co-inoculated with T. atroviride enhanced crop growth more than each of the microorganisms alone. Also Kabdwal et al (2019) observed best plant performance when multiple plant-beneficial microorganisms, including T. harzianum and AM fungi, were applied. Since soil-born beneficial microbes play a pivotal role in the functioning of plants by influencing their physiology and development (Mendes et al, 2013), further studies are needed to investigate the possible outcome when a plant is involved in interactions between different beneficial agents, including ectomycorrhizal fungi.…”
Section: Discussionmentioning
confidence: 96%
“…Meanwhile, the biocontrol mechanism of Trichoderma species is a complex process mediated by the secretion of extracellular enzymes, such as chitinases, β-glucanases, and proteinases, as well as secondary metabolites (Kumar et al, 2014b). Integrated treatment comprising of soil application of combined biocontrol agents was found very effective in reducing the plant mortality, promoting the plant growth, and increasing the yield (Jambhulkar et al, 2018;Kabdwal et al, 2019).…”
Section: Disease Intensitymentioning
confidence: 99%
“…According to Chandrashekara et al (2012), the degree of virulence plays a role in causing wilting symptoms rather than population density, while the virulence mechanism is closely related to several factors, such as host range, geographic distribution, physiological characteristics, and its adaptability to environmental temperature. The combined biocontrol agents were found very effective in reducing plant mortality (Kabdwal et al, 2019).…”
Section: Incubation Periodmentioning
confidence: 99%
“…Many studies have proved that PGPR have great potential to suppress the plant pathogens and increasing plant growth under greenhouse conditions (Kabdwal et al, 2019). These PGPR induce systemic resistance against a broad spectrum of pathogens due to their root colonization ability (Salem and Abd El-Shafea, 2018).…”
Section: Discussionmentioning
confidence: 99%